Klasifikasi Madu Berdasarkan Jenis Lebah (Apis dorsata versus Apis mellifera) Menggunakan Spektroskopi Ultraviolet dan Kemometrika - Diding Suhandy; Meinilwita Yulia; Kusumiyati Kusumiyati (Jurnal Ilmu Pertanian Indonesia, 2020)
In this research, spectral data in UV region (200-400 nm) alongside PCA and SIMCA chemometrics were used to classify two types of honey obtained from different honeybees (Apis dorsata versus Apis mellifera). A total of 200 Durian monofloral honey samples from Apis dorsata and 120 samples for Longan monofloral honey from Apis mellifera were prepared. Therefore, spectral data were recorded based on the following parameters: range of acquisition 200-400 nm, transmittance mode, and interval 1 nm. In addition, the original spectra were transformed using three different algorithms: moving average smoothing with 11 segments, standard normal variate (SNV), and Savitzky-Golay 1st derivative with 11 segments and 2 ordos. The result of PCA using transformed spectra in the range of 250-400 nm explained the possibility of clearly separating Durian and Longan honey along the PC1 axis, with 98% variance, while the SIMCA showed a 100% proper classification rate for all prediction samples. In addition, several important wavelengths were identified alongside high x-loadings values at 270 and 300 nm. These results were closely related to the absorbance of important phenolic compounds in honey, including benzoic, salicylic, and aryl-alyphatic acids. The results demonstrate a probability to establish simple and low-cost honey authentication systems, using UV spectroscopy and chemometrics on free-chemical in sample preparations. Keywords: authentication, Apis dorsata, Apis mellifera, SIMCA, UV spectroscopy